An Observational Cross-sectional Study on Dermatological Co-morbidities in Patients with Hemiplegia Secondary to Cerebral Stroke in a Tertiary Care Teaching Hospital in Eastern India - Subhransu Sekhar Jena (JCDR Research and Publications Private Limited, 2021)
Introduction: Hemiplegia due to cerebral stroke is associated with various dermatological co-morbidities, arising out of motor, sensory and autonomic dysfunctions. Aim: To find out the different dermatological conditions prevalent in patients of hemiplegia secondary to cerebral stroke. Materials and Methods: An observational cross-sectional study was conducted in the Department of Neurology in collaboration with the Department of Dermatology at Hi-Tech Medical College and Hospital, Bhubaneswar, Odisha from July 2017 to June 2020. Patients with hemiplegia of more than one month duration were included. The skin findings present before the neurological insult and patients with systemic conditions like atopic dermatitis, diabetes mellitus and thyroid disorders causing skin changes were excluded. Relevant tests for diagnostic confirmation of the skin lesions were done wherever needed. The software Statistical Package for the Social Sciences (SPSS) version 16.0 was used for the statistical analysis. Results: Study included 411 patients of cerebral stroke. A total of 382 (92.9%) patients were found to have dermatological manifestation. The male:female ratio in the study population was 2.6:1. A total of 549 and 128 skin conditions were diagnosed in the paralysed and non paralysed limbs, respectively. The common dermatological conditions diagnosed in the affected limbs were, xerosis {371 (97.12%)}, tinea corporis/cruris {61 (15.97%)}, onychomycosis {31 (8.12%)}, tinea pedis {28 (7.33%)} and nail dystrophy abnormalities {27 (7.07%)} patients. Conclusion: Knowledge of various dermatological conditions associated with hemiplegia helps in early intervention and better management during rehabilitation phase of patients with hemiplegia.